Limitations to oxygen transport and utilization during sprint exercise in humans: evidence for a functional reserve in muscle O(2) diffusing capacity - Calbet, José A. L. (J Physiol, 2015)
KEY POINTS: Severe acute hypoxia reduces sprint performance. Muscle [Formula: see text] during sprint exercise in normoxia is not limited by O(2) delivery, O(2) offloading from haemoglobin or structure‐dependent diffusion constraints in the skeletal muscle of young healthy men. A large functional reserve in muscle O(2) diffusing capacity exists and remains available at exhaustion during exercise in normoxia; this functional reserve is recruited during exercise in hypoxia. During whole‐body incremental exercise to exhaustion in severe hypoxia, leg [Formula: see text] is primarily dependent on convective O(2) delivery and less limited by diffusion constraints than previously thought. The kinetics of O(2) offloading from haemoglobin does not limit [Formula: see text] in hypoxia. Our results indicate that the limitation to [Formula: see text] during short sprints resides in mechanisms regulating mitochondrial respiration. ABSTRACT: To determine the contribution of convective and diffusive limitations to [Formula: see text] during exercise in humans, oxygen transport and haemodynamics were measured in 11 men (22 ± 2 years) during incremental (IE) and 30 s all‐out cycling sprints (Wingate test, WgT), in normoxia (Nx, [Formula: see text]: 143 mmHg) and hypoxia (Hyp, [Formula: see text]: 73 mmHg). Carboxyhaemoglobin (COHb) was increased to 6–7% before both WgTs to left‐shift the oxyhaemoglobin dissociation curve. Leg [Formula: see text] was measured by the Fick method and leg blood flow (BF) with thermodilution, and muscle O(2) diffusing capacity ([Formula: see text]) was calculated. In the WgT mean power output, leg BF, leg O(2) delivery and leg [Formula: see text] were 7, 5, 28 and 23% lower in Hyp than Nx (P < 0.05); however, peak WgT [Formula: see text] was higher in Hyp (51.5 ± 9.7) than Nx (20.5 ± 3.0 ml min(−1) mmHg(−1), P < 0.05). Despite a similar [Formula: see text] (33.3 ± 2.4 and 34.1 ± 3.3 mmHg), mean capillary [Formula: see text] (16.7 ± 1.2 and 17.1 ± 1.6 mmHg), and peak perfusion during IE and WgT in Hyp, [Formula: see text] and leg [Formula: see text] were 12 and 14% higher, respectively, during WgT than IE in Hyp (both P < 0.05). [Formula: see text] was insensitive to COHb (COHb: 0.7 vs. 7%, in IE Hyp and WgT Hyp). At exhaustion, the Y equilibration index was well above 1.0 in both conditions, reflecting greater convective than diffusive limitation to the O(2) transfer in both Nx and Hyp. In conclusion, muscle [Formula: see text] during sprint exercise is not limited by O(2) delivery, O(2) offloading from haemoglobin or structure‐dependent diffusion constraints in the skeletal muscle. These findings reveal a remarkable functional reserve in muscle O(2) diffusing capacity.